2023
DOI: 10.1001/jamanetworkopen.2023.46305
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Telemedicine Use and Glycemic Outcomes of Endocrinology Care for Patients With Type 2 Diabetes

Margaret F. Zupa,
Varsha G. Vimalananda,
Scott D. Rothenberger
et al.

Abstract: ImportanceTelemedicine can increase access to endocrinology care for people with type 2 diabetes (T2D), but patterns of use and outcomes of telemedicine specialty care for adults with T2D beyond initial uptake in 2020 are not known.ObjectiveTo evaluate patterns of telemedicine use and their association with glycemic control among adults with varying clinical complexity receiving endocrinology care for T2D.Design, Setting, and ParticipantsRetrospective cohort study in a single large integrated US health system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, the respondents with superior demographic (e.g., aged below 60 years old) and socio-economic factors (e.g., higher annual disposable income) from the national online survey were more likely to be deeply involved in IMSU (e.g., mental diseases: 374 times with 10.44%; telediagnosis: 378 times with 8.23%), which were consistent with previous studies [30][31][32][33][34]. Prior research has also indicated that the patterns of IMSU would be deepen in the patients with a chronic condition, nevertheless, in this study, patients suffering chronic diseases were less accessed to IMSU that those not suffering (35.59% vs. 40.56%) based on the provincial eld survey data, and patients suffering chronic diseases accessed to IMSU at a high frequency was lower than that at a low frequency (29.86% vs. 34.45%) based on the national online survey data [13,20,32,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 75%
“…However, the respondents with superior demographic (e.g., aged below 60 years old) and socio-economic factors (e.g., higher annual disposable income) from the national online survey were more likely to be deeply involved in IMSU (e.g., mental diseases: 374 times with 10.44%; telediagnosis: 378 times with 8.23%), which were consistent with previous studies [30][31][32][33][34]. Prior research has also indicated that the patterns of IMSU would be deepen in the patients with a chronic condition, nevertheless, in this study, patients suffering chronic diseases were less accessed to IMSU that those not suffering (35.59% vs. 40.56%) based on the provincial eld survey data, and patients suffering chronic diseases accessed to IMSU at a high frequency was lower than that at a low frequency (29.86% vs. 34.45%) based on the national online survey data [13,20,32,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 75%